SILICATE-PHOSPHATE INTERACTIONS IN SILICATE GLASSES AND MELTS: II. QUANTITATIVE, HIGH-TEMPERATURE STRUCTURE OF P-BEARING ALKALI ALUMINOSILICATE MELTS - Mysen B.O.; Cody G.D. (My University, 2001)
Structural data for glasses along the join 0.1[xNa2O-(1-x)Al2O3]-0.9SiO2 + 2 mol.% P2O5, obtained from multinuclear NMR and ab initio shielding calculations, have been combined with Raman spectroscopic data on the glasses at 25°C and melts to temperatures above 1200°C. The structural interpretation of those data is consistent with isolated PO4 and P2O7 complexes together with QPn (n = 1-4) species to be present in both glasses and melts. The QPn species consist of one PO4 group linked to the silicate network by 1 to 4 oxygen bridges (corresponding to n = 1-4 in the QP1 species).The principal solution mechanism of phosphorus in these glasses and melts can be described with a total of six different schematic expressions. These expressions are consistent with the observation from 29Si and 31P MAS-NMR that, for constant P2O5 content, increasing the alumina/alkali ratio leads to a decreased effect of phosphorus on silicate polymerization.Temperature-dependent interactions between phosphate solute and silicate solvent above the glass transition temperature have been identified. The types of interactions were separated into three composition ranges. For peralkaline melts, the phosphate species become more polymerized and the silicate species less polymerized, with increasing temperature: 2PO4+QSi4#P2O7+QSi3, and P2O7+5QSi4#2QP1+3QSi3, where QSin denotes speciation of silicate and QPn speciation of phosphate. The ΔH for these two reactions are 140 to 190 kJ/mol and ~65 kJ/mol, respectively. For compositions near meta-aluminate, the abundance of individual QPn species is temperature-dependent at temperatures above the glass transition, 2QP3#QP2+QP4, with ΔH = 13 to 19 kJ/mol. The abundance of silicate species is not affected by temperature for those compositions. For peraluminous melts, the phosphate species become less polymerized and the silicate species more polymerized with increasing temperature above the glass transition, QP4+QSi3#QP3+2QSi4, with ΔH = 13 to 23 kJ/mol.The structural data obtained in the high-temperature regime indicate that the melt structures resemble those of the glasses, although the abundance of individual melt species is temperature-dependent. Therefore, for peralkaline and peraluminous melts, properties that depend on melt polymerization become more pronounced if melt data, rather than structural data of glasses, were employed. For compositions near meta-aluminate, where neither phosphate nor silicate polymerization varies with temperature, properties that depend on melt polymerization are likely less sensitive to temperature.